Implementation of The Qira’ah Method in Arabic Language Comprehension: A Case Study at MI Al-Iman Merden - Najma Maulida; Khoirun Nisa’; Akhmad Shaiful Bakri (Abjadia : International Journal of Education, 2026)
Arabic language learning at the Madrasah Ibtidaiyah level still faces various problems, particularly in terms of reading and understanding Arabic texts. Students' lack of vocabulary and incorrect pronunciation make it difficult for them to understand the material. This study aims to describe the application of the qira'ah method and analyze the improvement in students' understanding of Arabic at MI Al-Iman Merden. This study uses a descriptive qualitative approach with field research. The research subjects include the principal, Arabic teachers, and students of MI Al-Iman Merden. Data collection techniques were conducted through interviews, observation, and documentation, while data analysis techniques used the Miles and Huberman interactive model. The results of the study show that the application of the qira'ah method is carried out through several stages, such as reading together, strengthening vocabulary, practicing pronunciation, and doing exercises. This method helps improve students' reading and comprehension skills in Arabic texts. However, there are still several obstacles, such as the level of reading fluency that is not yet optimal and limited learning aids. In general, the qira'ah method has a positive impact on improving students' understanding of Arabic at MI Al-Iman Merden.